MODEL PEMBELAJARAN TARI PENDIDIKAN PADA SISWA SD/MI SEMARANG - Jazuli, M (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
The underlying problem of this study is what learning model of Educational Dance is used for elementary school students in Semarang. This study employs qualitative approach using library research, interview, and direct observation as the methods of data collection. The subject of the study is the learning model of educational dance at elementary schools in Semarang district. Data analysis was conducted through descriptive analysis method. The study shows that learning model used for educational dance at elementary school is explorative model using observation evaluation technique. The learning model includes: first, materials of movement lesson that covers body realization, mastery of basic movements, and movement development. Second, movements that reflect thought, feeling, and communication medium. Third, the direction of dance lesson covers aspects such as delight, creativity, communication, and aesthetics. Fourth, students’ character development that embeds in the learning process implicates in students’ attitude, such as the growing self-confidence, concern, tolerance, and responsibility. It is then concluded that the components of learning model of educational dance for elementary school, based on regulation number 19 article number 19 year 2005, are met in the explorative model because it shows the existence of dimensions that are interactive, inspiring, fun, challenging, motivating students to actively participate, and giving rooms necessary for initiative, creativity, and autonomy in accordance to students’ talent, interest, physical and psychological development. Kata kunci : model pembelajaran, tari pendidikan